Analysis of the propagation of a spherical wave with finite amplitude in an ideal gas by the renormalisation method - ROSZKOWSKI, Czesław Adam (Archives of Acoustics, 1983)
This paper gives an approximate solution of the hydrodynamic equations in the case of a spherical wave with finite amplitude. Using the perturbation renormalisation method it gives the desired description of the acoustic field of a spherical wave generated by a spherical source which pulsates monochromatically with finite amplitude in an infinite, lossless gaseous medium. The solutions obtained for the acoustic velocity and the acoustic pressure have the form of asymptotic expansion of the first order relative to a small perturbation parameter and are valid both for the near and the far field. The analysis of the acoustic field has for the first time been performed directly using the perturbation renormalisation method for a spherical wave.